A method for measurement of the hypertrophic first metatarsal medical eminence on foot radiographs - A reliability study with surgical implications - Armanasco, P.; Briffa, Kathy; Pang, N. (Scientific Research Publishing Inc, 2014)
Background: It has been suggested that hypertrophic eminence on the medial head of the first metatarsal is a component of the patho-anatomy of hallux valgus. However, research findings in this area are inconsistent, possibly due to differences in methods in identifying and measuring the medial eminence. To date, reliability of any method of measurement has not been reported. The purpose of this study was to determine the reliability of measurement of the medial eminence on medial oblique and dorsoplantar radiographs using a previously described geometric technique. Methods: To evaluate the reliability of a method of measurement of the medial eminence of the first metatarsal duplicate standardized dorsoplantar and medial oblique radiographs were taken of one foot of 15 subjects. The feet included both rectus feet and subjects with hallux valgus. The medial eminence was measured on the digital images using Inteleviewer 2.5 (Intelerad medical systems incorporated, Montreal, Quebec) software. Observer 1 measured one randomly selected image from each subject to determine inter-observer reliability. Observer 2 measured all images to determine the overall inter-observer reliability. Reliability was calculated using intra-class correlation coefficients (ICC).Results: The mean projection of the medial eminence ranged from 0.39 to 0.44 cm in both views. The ICCs were calculated for the dorsoplantar view and the 2 medial oblique view measures between observers. They ranged from 0.76 intra-rater and 0.86 inter-rater in the dorsoplantar view to 0.80 intra-rater and 0.90 inter-rater in the medial oblique view indicating good reliability in all measures. The average of the 4 oblique views also showed a high level of reliability with a coefficient of 0.96. Conclusions: The medial eminence can be reliably measured in the medial oblique and dorsoplantar view using the described technique. The medial oblique and the dorsoplantar views are valuable and reliable projections for visualising the dorso medial aspect of the first metatarsal.